The prevalence of undiagnosed Prediabetes/type 2 diabetes, prehypertension/hypertension and obesity among ethnic groups of adolescents in Western Canada - Shelley Spurr; Jill Bally; Carol Bullin; Diane Allan; Erick McNair (BMC, 2020)
Abstract Background An increased incidence of type 2 diabetes in youth is occurring worldwide. While diverse ethnic groups are disproportionately affected by type 2 diabetes, studies that explore ethnic differences and undiagnosed prediabetes/type 2 diabetes in adolescents are scarce. This paper compares the prevalence of undiagnosed prediabetes and type 2 diabetes and the associated risk factors among various ethnic groups of adolescents living in Western Canada. Methods The data for this study were derived from two previous studies in which 396 adolescents, aged 14 to 19 years and living in a western Canadian province, were screened for undiagnosed prediabetes, diabetes, and any associated risk factors. Risk was determined by demographics, family history, anthropometric measurements (body mass index, BMI), blood pressure (BP), and HbA1c. Descriptive and inferential statistics (SPSS) were used to establish both risk and prevalence for prediabetes and type 2 diabetes. Chi-square analyses were done to determine if the risk factors occurred at higher frequencies in certain ethnicities. Results Based on BP, BMI, and HbA1c measurements, several statistically significant differences were identified in relation to ethnicity. Many of the adolescents had increased HbA1c levels, with 27.3% considered high risk and 2.3% in the prediabetes range; these high risk and prediabetes groups were heavily represented by Filipino (46%), Indigenous (22%), and European (10%) adolescents. Notable prevalence of prehypertension (17.7%) and hypertension (21.7%) were reported in European (59%) followed by Filipino (50%) and Indigenous (26%) adolescents. Higher numbers of adolescents in the European and Filipino ancestry groups had two or more risk factors (BP, BMI, & HbA1c) for developing type 2 diabetes in relation to the adolescents from the Indigenous group. Conclusions Ethnic adolescent groups demonstrate a notable prevalence of undiagnosed prediabetes and type 2 diabetes. Specifically, a significant number of Filipino adolescents had both increased HbA1c and blood pressure that has gone undetected. Earlier onset of type 2 diabetes is congruent with an increased risk of developing diabetes-associated complications and, ultimately, diabetes-related morbidity and mortality at a younger age. Future studies should explore how genetic and/or environmental factors among ethnic groups may contribute to early onset hypertension and prediabetes/type 2 diabetes.